1995
DOI: 10.1002/jmor.1052240304
|View full text |Cite
|
Sign up to set email alerts
|

Sperm storage in the oviduct of the tropical rock lizard, Psammophilus dorsalis

Abstract: The female rock lizard, Psammophilus dorsalis (Agamidae), lays multiple clutches of eggs over a period of 6 months (June-December). The later clutches of eggs are presumably fertilized by sperm stored from earlier matings, since testes and epididymides are regressed after August. Sperm storage is seen in pockets of the anterior vaginal region of the oviduct. Sperm recovered from the uterovaginal region are intact and motile. Discrete granules resembling the secretory granules present in the vas deferens also o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Cuellar, 1966; King, 1977). However, as most tropical lizards have synchronized reproductive cycles between sexes, sperm storage may not be essential (Srinivas et al., 1995). The increase in frequency of reproduction seems to represent the form of compensation for the small and fixed clutch sizes of this species, since there is no correlation between egg volume and female body size.…”
Section: Discussionmentioning
confidence: 99%
“…Cuellar, 1966; King, 1977). However, as most tropical lizards have synchronized reproductive cycles between sexes, sperm storage may not be essential (Srinivas et al., 1995). The increase in frequency of reproduction seems to represent the form of compensation for the small and fixed clutch sizes of this species, since there is no correlation between egg volume and female body size.…”
Section: Discussionmentioning
confidence: 99%
“…In externally fertilizing echinoderms and salmon fish, the initiation of sperm motility is mediated by several types of cations (Lee et al, 1983;Morisawa and Suzuki, 1980), whereas it occurs via changes in In internally fertilizing vertebrates, motility is initiated or activated in sperm stored in the female"genital tract (Suarez, 1987;Gist and Jones, 1989;Smith and Yanagimachi, 1991;Suarez et al, 1991;Baskt, 1992;Birkhead et al, 1993;Srinvas et al, 1995). In mammals, the caudal isthmus of the oviduct is the sperm storage site (Smith and Yanagimachi, 1991) from which sperm are released into the lumen with hyperactivated motility (DeMott and Suarez, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…However, in the present study the stored sperm was normal with a structural integrity. The fertilizing ability of stored sperm has been demonstrated in C. versicolor (Shanbhag and Prasad, ) and similarly, motile sperm have been also recovered from the oviduct of another sympatric species, the rock lizard, Psammophilus dorsalis (Srinivas et al, ). Our previous studies (Kumari et al, ) have shown that a large proportion of females in the natural population of C. versicolor are found with oviductal eggs over an extended period (October to next January), when complete testicular regression is observed, providing strong circumstantial evidence for the hypothesis that the stored sperm is used for fertilizing the eggs laid in multiple clutches without repeated mating (Kumari et al, ).…”
Section: Discussionmentioning
confidence: 87%